2020
DOI: 10.1055/s-0040-1701196
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Interobserver Reliability of Magnetic Resonance Imaging for Placenta Accreta Spectrum Disorders

Abstract: Objective This study aims to define the accuracy, predictive value, and interobserver reliability of magnetic resonance imaging (MRI) in the diagnosis of placenta accreta spectrum (PAS) disorders. Study Design Two experienced radiologists independently interpreted the MRI studies of patients with possible PAS from two referral centers. Radiologists were blinded to sonographic and clinical information. We calculated diagnostic testing characteristics and kappa statistics of interobserver reliability f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The main MRI features of accreta placentation include abnormal uterine bulging, dark intraplacental bands on T2-weighted imaging, heterogeneous signal intensity within the placenta and disruption of the uteroplacental zone [40][41][42][43][44][45][46][47][48] . Recent data suggest that the finding of a placental budge on MRI has the highest sensitivity for the diagnosis of severe PAS 43 .…”
Section: Prenatal Imaging Diagnosis Of Pasmentioning
confidence: 99%
“…The main MRI features of accreta placentation include abnormal uterine bulging, dark intraplacental bands on T2-weighted imaging, heterogeneous signal intensity within the placenta and disruption of the uteroplacental zone [40][41][42][43][44][45][46][47][48] . Recent data suggest that the finding of a placental budge on MRI has the highest sensitivity for the diagnosis of severe PAS 43 .…”
Section: Prenatal Imaging Diagnosis Of Pasmentioning
confidence: 99%
“…This study had two main ndings. Firstly, the interobserver agreement of texture analysis for the diagnosis of PAS disorders was substantial, which was a little higher than that of MRI [9].Secondly, although interobserver agreement of texture analysis and MRI for the diagnosis of PAS disorders was similar, the AUC, sensitivity and speci city of texture analysis were perfect and higher than previously reported MRI ndings [9,10].…”
Section: Main Ndingsmentioning
confidence: 57%
“…It is therefore crucial for radiologists to be involved in the multidisciplinary team and to provide standardized diagnostic assessment of PAS disorders [8]. Ultrasonography (US) had a lower diagnostic accuracy in detecting PAS disorders than MRI, which had a sensitivity 66%, speci city 71% and accuracy 68% [9,10]. Even though US is the frontline imaging modality for the evaluation of PAS disorders [11], MRI is used as a problem-solving tool for equivocal sonographic ndings or suspicion of posterior/lateral placental extension [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 summarizes these findings. A more recent study reported lower accuracy of MRI than previously reported, with a sensitivity and specificity of 66% and 71% for PAS and 85 and 79% for percreta, respectively [68 ▪ ].…”
Section: Mri Diagnosismentioning
confidence: 77%